The roar and the silence : a history of Virginia City and the Comstock Lode - James, Ronald M. (Ronald Michael), 1955- (Wilbur S. Shepperson series in history and humanities (Unnumbered), 1998)
The Roar and the Silence chronicles the area's history from its earliest days through the early twentieth century, when the lode finally gave out ant the Comstock sank into silent decay, and up to the present, when Virginia City and its environs found new life, first as a community of bohemians and artists, and more recently as a tourist attraction offering a taste of the frontier experience to visitors from around the world. James's text brings the Comstock to life again in all its complexity and boom-and-bust excitement. This book offers a wealth of new information and insight into the history of one of the Old West's most storied areas.